(untitled) (Journal of Universal Science Research, 2023)
Crack occurrence in reinforced concrete should be minimized for both durability and economical reasons as crack repair is costly. Autogenous repair, or self-healing, of concrete would save a substantial amount of money, as manual inspection and crack repair could be minimized. Thus, a reliable self-healing mechanism for concrete would not only result in more durable structures, but would also be beneficial for the global economy. This study exploited the potential to apply calcite-precipitating bacteria as a crack-healing agent in concrete. The potential of different species to precipitate calcite, produce endospores, survive concrete-production, and heal cracks by sealing them with calcite was investigated. Furthermore, the mechanical properties of ‘bacterial concrete’ were tested. ESEM studies showed that alkali-resistant spore-forming bacteria embedded in the concrete matrix can precipitate substantial amounts of calcite. The bacterial approach thus seems a highly promising mechanism to mediate self-healing in concrete structures.